A Seasonal Model of Nitrogen Isotopes in the Ice Age Antarctic Zone: Support for Weakening of the Southern Ocean Upper Overturning Cell. Issue 12 (21st December 2018) - Kemeny, P. C.; Kast, E. R.; Hain, M. P.; Fawcett, S. E.; Fripiat, F.; Studer, A. S.; Martínez‐García, A.; Haug, G. H.; Sigman, D. M.
Abstract: In the Antarctic Zone of the Southern Ocean, the coupled observations of elevated diatom‐bound 15 N/ 14 N (δ 15 Ndb ) and reduced export production during the ice ages indicates more complete nitrate (NO3 − ) consumption. This evidence points to an ice age decline in gross NO3 − supply from the deep ocean to the surface wind‐mixed layer, which may help to explain the reduced CO2 levels of the ice age atmosphere. We use a seasonally resolved, two‐layer model of the N isotopes in the Antarctic Zone upper ocean to quantify the ice age decline in gross NO3 − supply implied by the data. When model parameters are varied to reflect reduced gross NO3 − supply, the concentration of wintertime upper ocean NO3 − is lowered, but with a much weaker increase in NO3 − δ 15 N than predicted by analytical models such as the Rayleigh and steady state models. Physical mixing is the dominant cause, with a modest contribution from foodweb dynamics. As a result, the observed δ 15 Ndb rise of 3‰–4‰ must be explained mostly by a greater summertime increase in NO3 − δ 15 N during the ice ages. The high degree of NO3 − consumption required to generate this summertime δ 15 N rise indicates a >80% reduction in gross NO3 − supply. Half or more of the modern gross NO3 − supply is from wind‐forced Antarctic upwelling that drives the upper cell of Southern Ocean overturning. Thus, the decrease in NO3 − supply cannot be achieved solely by a decline in vertical mixing or wintertime convection; rather, it requires an ice age weakening of the upper cell. Key Points: A two‐layer model of Antarctic Zone seasonality that includes upper ocean N cycling captures key N isotopic patterns The model indicates that an ice age rise of 3‰‐4‰ in diatom‐bound δ 15 N requires a >80% reduction in gross NO3 − supply from deep waters This large change implies a weakening of the upper cell of global ocean overturning that passes through the Antarctic surface